The determination of ventilatory inefficiency at rest in COPD: the expected parameter - Caviedes, Iván; Soto, Rodrigo; Herth, Felix (The European respiratory journal, 2020)
Tweetable abstract ERSpublications - click to tweetThe assessment of V′E/V′CO2 ratio at rest as a representation of ventilatory inefficiency is a simple and relevant determination in the evaluation of lung function in patients with COPD, additive to parameters of lung hyperinflation on physical limitation https://bit.ly/2EYMGdx
Gesehen am 05.11.2020